Слов'янські автохтонні власні особові імена-композити в чеських і українських мовах - Осташ, Л.Р. (Мовознавство, 2002)
Проаналізовано компоненти слов'янських автохтонних власних особових складних імен (композитів) у прізвищах чехів і українців. Виділено однакові компоненти, що активно вживалися в обох антропоніміях під час творення прізвищ. Констатовано певну специфіку визначення походження та первісного значення прізвищ, утворених від слов'янських автохтонних імен-композитів. In the article the components of Slavonic autochthonous proper personal compound names (composites), which occur in family names of the Czechs and the Ukrainians, are analyzed. Those equal components, which were actively used in anthroponomy of both languages in the process of family name creation, are distinguished. Attention is attracted to similarity of models in transformation of these names into family names. Lists of suffixes, which were utilized by each of both languages in the process of forming family name from these proper personal names, are analyzed. Some specificity of determination of origin and initial meaning of family names formed from Slavonic autochthonous names-composites is established. In particular, it is assumed that there are several possible sources of their origin and ways of creation.